2013
DOI: 10.1631/jzus.b1200218
|View full text |Cite
|
Sign up to set email alerts
|

Association of CASP9, CASP10 gene polymorphisms and tea drinking with colorectal cancer risk in the Han Chinese population

Abstract: Abstract:The initiators caspase-9 (CASP9) and caspase-10 (CASP10) are two key controllers of apoptosis and play important roles in carcinogenesis. This study aims to explore the association between CASPs gene polymorphisms and colorectal cancer (CRC) susceptibility in a population-based study. A two-stage designed population-based case-control study was carried out, including a testing set with 300 cases and 296 controls and a validation set with 206 cases and 845 controls. A total of eight tag selected single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 43 publications
(42 reference statements)
0
7
0
Order By: Relevance
“…Given the role of CASP7 in apoptosis and inflammation, the associations among CASP7 and autoimmune diseases and cancer susceptibility are important. Their relevance has been reported in insulin-dependent diabetes mellitus, rheumatoid arthritis, childhood leukemia, and different types of human cancers [18, 21]. Soung et al found that a CASP7 gene inactivating mutation (70 Cys to Tyr mutant) could lead to loss of apoptotic function [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the role of CASP7 in apoptosis and inflammation, the associations among CASP7 and autoimmune diseases and cancer susceptibility are important. Their relevance has been reported in insulin-dependent diabetes mellitus, rheumatoid arthritis, childhood leukemia, and different types of human cancers [18, 21]. Soung et al found that a CASP7 gene inactivating mutation (70 Cys to Tyr mutant) could lead to loss of apoptotic function [18].…”
Section: Discussionmentioning
confidence: 99%
“…Single nucleotide polymorphisms (SNPs) influence the expression or the activities of caspase enzymes. Several CASP genes polymorphisms have been found to be associated with kinds of cancers [1721] and autoimmune inflammatory diseases, such as rheumatoid arthritis [5], coronary artery disease [22], Kawasaki disease [23], acute pancreatitis [24], and ischemic stroke [25], but the relationship with psoriasis has not been studied. And gene expression profiles showed significant differences in the expression of CASP7 and CASP8 between psoriatic lesions and psoriatic nonlesions.…”
Section: Introductionmentioning
confidence: 99%
“…For example, CASP3 is reported to be referred to the spread of tumor cellulas in gastrointestinal tumors, and targeted CASP3 therapy can inhibit the development of cancer cells [30]. CASP9 is a protein-coding gene, and many reports have shown that CASP9 gene polymorphisms are associated with increased tumor risk, but this conclusion is controversial [31,32]. In gliomas, high expression of PYCARD is related to poor patient prognosis and is used as an independent predictor of chemoresistance [33].…”
Section: Discussionmentioning
confidence: 99%
“…Studies about an association of CRC with genetic polymorphisms in the CAS9 and CAS10 genes-CRISPR associated-reported a protection against mobile genetic elements [122], against PLA2G4A-phospholipase A group IVA-gene associated inflammation [123], and increased XPCxeroderma pigmentosum associated mutation repair ( [124], see Table 3); all three studies included GT drinking as a modifying factor for the association of CRC with the genotypes; neither study confirmed effects of the polymorphisms studied. In a similar venue Jing et al [125] studied single nucleotide polymorphisms.…”
Section: Crc-association Studiesmentioning
confidence: 96%